PENDUGAAN INTERSEPSI TEGAKAN AKASIA (Acacia mangium) DI ARBORETUM FAKULTAS KEHUTANAN UNIVERSITAS LAMBUNG MANGKURAT BANJARBARU - Lusi Anggraeni; Badaruddin Badaruddin; Syarifuddin Kadir (Jurnal Sylva Scienteae, 2020)
The purpose of this research is to know the magnitude of water escapes, stem and flow interception from the stands of Acacia (Acacia mangium) and compare the magnitude of water heading lolosan, stem and flow interception according to diameter class stands. Prediction of the intercept using 12 sampling the stands with a certain diameter 12 consists of 3 tree forest tree with a diameter of 10-20 cm, 3 cm in diameter and stands are >20-30 cm, 3 stands with a diameter of >30-40 cm and 3 trees with a diameter of >40 cm. Data taken the day after day of rain in the morning. The data were taken over a period of 2 months of research. The results of this research the water escapes the largest header is present on trees with a diameter of >40 cm of 10,1573 mm and the lowest on the diameter of 10-20 cm has an average 9,0364 mm. stem flow value is present on the largest diameter of >30-40 cm of 0,0088 mm and the lowest value in the diameter >40 cm of 0,0025 mm. The greatest value of the interception is present on 10-20 cm diameter of 5,0406 and the lowest value on the diameter of the >30-40 of 3,5874.Key words: Acacia trees; Through fall; Steam flow; Interception